Synthesis and evaluation of novel 2, 4-diaminopyrimidines bearing bicyclic aminobenzazepines for anaplastic lymphoma kinase (ALK) inhibitor. Issue 18 (15th September 2015) - Kang, Ga Ae; Lee, Minji; Song, Dawn; Lee, Heung Kyoung; Ahn, Sunjoo; Park, Chi Hoon; Lee, Chong Ock; Yun, Chang Soo; Jung, Heejung; Kim, Pilho; Ha, Jae Du; Cho, Sung Yun; et al.
Graphical abstract: Abstract: A series of novel 2, 4-diaminopyrimidine compounds bearing bicyclic aminobenzazepine were synthesized and evaluated for their anti-ALK activities. The activities of these compounds were confirmed in both enzyme- and cell-based ALK assays. Amongst compounds synthesized, KRCA-0445 showed very promising results in pharmacokinetic study and in vivo efficacy study with H3122 xenograft mouse model.